Enhancing Learning with Liveworksheet: Perceptions, Advantages, Disadvantages, and Impacts - Yuri Widiantho; Nadia Virdhani Hia; T. Silvana Sinar (Talenta Publisher, 2023)
This article explores the concept of Liveworksheet websites and provides a comprehensive analysis of their advantages and disadvantages for students and teachers. Drawing on previous studies and explanations, the article highlights the benefits of Liveworksheet websites, including personalized learning, immediate feedback, increased engagement, progress tracking, flexibility, and accessibility. The data presented supports the positive impact of Liveworksheet websites on teaching and learning experiences, enabling students to take ownership of their learning journey and improve academic performance. However, potential challenges such as the need for internet technological issues should be considered. By understanding and addressing these drawbacks, educators and students, can effectively utilize Liveworksheet websites to create an interactive and adaptable learning environment. This article serves as a guide for educators, providing insights on how to leverage the potential of Liveworksheet websites and enhance student learning outcomes